Training Needs of Fish Farmers for the Development of Fisheries and Aquaculture in Meghalaya - Niangti, Wandame; Singh, Yumlembam Jackie; Lahiri, Biswajit; Upadhyay, Anil Datt; Pal, Prasenjit; Meinam, Martina; Bharati, Huirem; Monsang, Maitarambum Wartung (Indian Journal of Extension Education, 2025)
The study assessed the training needs of fish farmers in the West Garo Hills and Ri-Bhoi districts of Meghalaya from the data collected with pre-tested semi-structured interview schedule from a randomly selected sample of 90 respondents from eight villages across four blocks. Training needs were prioritised using the Training Need Index (TNI). The study revealed that the majority of respondents were middle-aged (71.11%), had a secondary school education (37.78%), belonged to nuclear families (48.89%), and had up to 5 years of experience in fish farming (80%). Most respondents earned an annual income of up to ¹ 50,000 from fish farming (83.33%). The top areas of need were aquaculture (TNI 100.00), hatchery management, fish seed production, nursery management (TNI 97.03), and disease prevention and control in fish (TNI 96.29). Other needs included fish processing (TNI 70.00), pond construction and equipment management (TNI 62.2), recreational fisheries (TNI 56.59), and communication tools for fish farmers (TNI 48.51). The key training requirements were carp culture, broodstock maintenance and breeding, fish disease management, value addition, hatchery construction, recreational pond development, and leveraging social media for information sharing. These findings emphasise the need for targeted training programmes to enhance fish production and productivity.
Keywords: Training needs assessment; Fish farmers; Meghalaya; Socio-economics